EP.TU.153Face to face teaching in the covid era: Basic Surgical Skill Development. (28th October 2021) - Kirchhoff, Chris; Davis, Heather
Abstract: Aims: According to literature, newly qualified doctors are at risk of being unable to perform practical procedures safely. This has been exacerbated by the disruptions to training and education which the covid-19 pandemic has caused. This intensive course has been developed to improve basic surgical skills and improve confidence in simple wound closure, to mitigate these disruptions. Methods: Candidates attended a three-part course in small groups, where they learned hand ties, basic laparoscopic skills and wound closure on animal models. Self assessment data were collected pre and post workshop on a Likert scale. All data was assessed using basic descriptive analysis. Results: Data was collected from 13 participants (M:F, 5:8) at the level of foundation year 1(61.5%, n=8) and foundation year 2(38.5%, n=5). Only 38.5% (n = 5) had previous basic surgical skills training. Our delegates reported an improvement in the following surgical skills: suturing (n = 11, 84.6%), hand tying (n = 10, 76.9%), laparoscopic skills (n = 10, 76.9%). Overall 61.5% (n = 8) of our delegates reported an improvement in all three domains. Conclusions: Participants reported limited exposure prior to this course despite successfully completing an undergraduate curriculum. Overall, participants' self-scores improved in all three taught surgical skills. We believe ourcourse is a practical and reproducible solution to help bridge training gaps, which can be safely conducted with social distancing measures.